Political Flow in the 2009 Election (Study on Changes in the Platform for the Prosperous Justice Party in the 2009 Election) - Muhammad Alatas (The International Journal of Politics and Sociology Research, 2021)
The purpose of this study is to describe the dynamics of Indonesian Islamic politics that occurred in the 2009 general election (election). Given that since the 1998 reforms were rolled out, it seems to have reopened the pages of history about the flow patterns that were formed in the early days of independence. In contrast to the previous two elections, where the nuances of sectarianism were very strong, in the 2009 elections, every political party began to realize that in the context of a pluralistic society like Indonesia, it would seem odd to only rely on religio-ideological cleavages as icons for mobilizing and maximizing votes. Because by opening up, each party can gain as much support as possible from various entities, races, religions and groups in order to rule this country. And in general, this research aims to see the pattern of political flow that occurred in the 2009 election; a study on changes to the Prosperous Justice Party Platform in the 2009 General Election.